Comparison of the effectiveness of diode laser, fluoride varnish, and their combination in treatment of dentin hypersensitivity: a systematic review of randomized clinical trials - Manijeh Mohammadian; Manijeh Mohammadian; Nima Jalouti; Mohsen Yazdanian; Elham Keykha; Samira Hajisadeghi (Frontiers in Oral Health)
Background and aimDentin hypersensitivity (DH) has long been a challenging condition, with many treatment methods showing limited success. However, the emergence of laser therapy, particularly the significant potential of diode laser (DL) and sodium fluoride (NaF) varnish, has sparked new hope. This research is a significant step towards a more effective treatment for DH, aiming to evaluate the promising potential of DL in treating DH, both independently and in combination with fluoride varnish. By delving into this research, you are investing your time in understanding a crucial advancement in the field of dentistry.MethodsA comprehensive search was conducted across the PubMed, Scopus, and Web of Science databases, including studies published up until May 2024. Randomized clinical trials that assessed DH using a visual analog scale (VAS) score were included. Data on participant demographics, treatment types, and VAS scores were extracted by two reviewers. The risk of bias was assessed using the revised Cochrane risk-of-bias instrument for randomized trials (RoB-2).ResultThree studies met the inclusion criteria, comparing NaF varnish, DL, and their combination. Both DL and the combination of DL and NaF varnish were more effective than NaF varnish alone in reducing DH. The combined treatment showed marginally superior outcomes compared to DL alone. Significant reductions in DH were observed across all treatment groups, with the combination therapy demonstrating the most substantial and consistent improvement.ConclusionDiode laser therapy, particularly when combined with NaF varnish, represents a promising treatment approach for DH, offering superior efficacy over NaF varnish alone. These findings suggest that combination therapy may provide longer-lasting relief, with implications for improving clinical outcomes in DH management.